The Analysis Of The Main Character In The Novel “KEBERANGKATAN” Works N.H. Dini - Annim Hasibuan (CV. AFDIFAL MAJU BERKAH, 2022)
The problem of this research is: “how does the main character in the novel “Keberangkan” works N.H. Dini?”. The purpose of this study is: “to describe the main character in the novel “Keberangkatan” works N.H.Dini”. The method used in this research is a qualitative research method where this method is commonly used in these kinds of research in social sciences, humanities, and sciences legal. Sources of data in this research is the text in the novel “keberangkatan” works N.H. Dini. Data collection was performed with the technique of the literature and the technique of document analysis. This technique is done by reading the data with the aim of identifying data in accordance with the theory that is used While the data analysis in this paper utilizes ways of interpretation in the form of descriptive analysis with how to (a) identify the elements that exist in the novel, (b) identification characterizations in the novel, and (c) provide an analysis of the characterizations in the novel. The results showed that the novel “ keberangkan” work N.H. Dini this indicates the presence of the antagonist and the protagonist in the novel.